Think twice before taking bribe: the binary of corruption and dignity - Hasan, Md. Mahmudul (OnIslam.net, 2015)
It is widely known that bribery is a sophisticated but more pernicious way of stealth and robbery. It is hated and discouraged both in religious and secular terms. But the religion-neutral reasoning and argument against this social disease does not seem to prevent the dishonest from making unlawful money through bribery and graft. Given the fact that, both religious and non-religious arguments against bribery do not seem to work, I share an anecdote below, hoping that it will make the current and would-be corrupt think twice before they take bribe.